Updates on the taxonomy and distribution of Gastroserica Brenske, 1897, Microserica Brenske, 1894, and Moronoserica Ahrens, Lukic & Liu, 2023 (Coleoptera: Scarabaeidae: Sericinae: Sericini) - Ahrens, Dirk; Pham, Phu (Zootaxa, 2023)
A short update on the taxonomy of Gastroserica Brenske, 1897 is given. Two new species of the subgenus Helioserica Ahrens, Lukic & Liu, 2023, and one new species of the nominotypical subgenus are described: Gastroserica (H.) kachin Ahrens & Pham, new species (from Myanmar), G. (H.) horii Ahrens & Pham, new species, and G. (G.) muongphangensis Ahrens & Pham, new species (both from Vietnam). One name is synonymized: Gastroserica (G.) wenzhui Liu & Ahrens, 2014 (= Gastroserica skalei Ahrens & Fabrizi, 2018, new synonymy). Additional new records of the recently revised Microserica Brenske, 1894, and Moronoserica Ahrens, Lukic & Liu, 2023 as well as of Gastroserica are given. The diagnostic characters of the new taxa are illustrated. A corrective note for Ahrens et al. (2023) is also given, regarding the omitted but previously published synonymy of Microserica pusilla (Thunberg, 1818) (= Microserica compressipes (Weidemann, 1823)).